Growth medium with low serum and transforming growth factor beta 3 promotes better chondrogenesis of bone marrow-derived stem cells in vitro and in vivo - Alfaqeh, Hamoud Hussein Mohammed; Chua, K. Hui; Saim, Aminuddin; Idrus, Ruszymah (Riyadh Armed Forces Hospital, 2011)
Adult mesenchymal stem cells are candidate cells for cartilage tissue engineering due to their ability to undergo chondrogenic differentiation after extensive expansion, and induced with growth factors.1 Sustained delivery of transforming growth factor beta (TGF-ß)3 induces differentiation of human bone marrow-derived stem cells (BMSCs) into chondrocytes.2 Bone marrowderived stem cells undergo chondrogenesis in a variety of culture conditions, and the addition of TGF-ßs has generally enhanced chondrogenesis regardless of culture method.3 "echondrogenic differentiation of BMSCs induced by growth factors, such as TGF-ß3, and insulin like growth factor (IGF)-1 can inhibit the instability of the chondrocyte phenotype, promote extracellular matrix secretion, and maintain cartilage matrix macromolecules during chondrogenesis.4 "e shift from TGF-ß3 to IGF-I at week 3 resulted in a significant increase of cartilage-like extracellular matrix.5 "is study aimed to examine the effect of TGF-ß3 and TGF-ß2 on BMSCs chondrogenesis in vitro and in vivo.